2003
DOI: 10.1021/bi027138+
|View full text |Cite
|
Sign up to set email alerts
|

Copper Coordination in the Full-Length, Recombinant Prion Protein

Abstract: The prion protein (PrP) binds divalent copper at physiologically relevant conditions and is believed to participate in copper regulation or act as a copper-dependent enzyme. Ongoing studies aim at determining the molecular features of the copper binding sites. The emerging consensus is that most copper binds in the octarepeat domain, which is composed of four or more copies of the fundamental sequence PHGGGWGQ. Previous work from our laboratory using PrP-derived peptides, in conjunction with EPR and X-ray crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
339
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 274 publications
(358 citation statements)
references
References 44 publications
18
339
0
1
Order By: Relevance
“…Clearly, the results reported here require not only confirmation in full-length PrP but also an assessment of the influence of non-octarepeat coordination sites (20,28) and other features that may affect Cu 2+ uptake. With regard to octarepeat coordination, however, our previously published experiments on full-length PrP Since the discovery of the physiological connection of PrP to copper, there have been intensive efforts to determine the precise Cu 2+ affinity (8,10,(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 81%
“…Clearly, the results reported here require not only confirmation in full-length PrP but also an assessment of the influence of non-octarepeat coordination sites (20,28) and other features that may affect Cu 2+ uptake. With regard to octarepeat coordination, however, our previously published experiments on full-length PrP Since the discovery of the physiological connection of PrP to copper, there have been intensive efforts to determine the precise Cu 2+ affinity (8,10,(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 81%
“…These models, which were elaborated considering the substoichiometric complexations of Cu(II) per octarepeat, differ in the final assembly, being either helical or planar. The models of the second group, which corresponds to full site occupancy, are formed in the crystal structure of Cu(II) in complex with the minimal site HGGGW and are then considered to be applicable to the fully saturated SHaPrP-(23-231) (17,19). In these fully saturated forms, the Cu(II) geometry is one of penta-coordination with the nearly equatorial ligation to the ␦1 nitrogen of the His, the deprotonated amide nitrogens of the two sequential Gly residues, the amide carbonyl oxygen of the second Gly * This work was supported in part by Ministerio de Ciencia y Tecnología of Spain (MCYT) Grants BIO2000-1664, BIO-2000-0175-P4, and BIO2003-00285, and a NeuroPharma S.A.-CSIC contract (all to M. G.).…”
mentioning
confidence: 99%
“…These residues are located within the tandemly repeated PHGGGWGQ sequence known as the octarepeat and at the flexible hinge that connects the N-terminal and C-terminal domains (16 -20). In addition to these, other minor Cu(II)-binding sites in the C-terminal globular domain have been reported (19,21,22). Studies with PrP C models, as synthetic peptides and recombinant forms, have shown binding stoichiometries of up to one Cu(II) per octarepeat motive in a process in which the interaction among cation sites, measured as positive cooperativity, appears when the number of sites is higher than two (15,18,(22)(23)(24).…”
mentioning
confidence: 99%
“…PrP binds copper with low-micromolar affinity and in a pH-sensitive manner via N-terminal histidine-containing octapeptide repeats (Jackson et al, 2001;Kramer et al, 2001;Burns et al, 2002). Binding of Cu ++ to the C-terminal portion of PrP in vivo seems unlikely, but it has been suggested by experiments using amino-terminal truncations of the protein (Burns et al, 2003).…”
Section: Introductionmentioning
confidence: 99%